1999
DOI: 10.1177/01939459922044117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traumatic Events, Social Support, and Self-Efficacy on Adolescents’ Self-Health Assessments

Abstract: The purpose of this study was to examine the relationship between adolescents' exposure to traumatic events and their self-health assessments, and to examine the protective effects of social support and self-efficacy on this relationship. Survey results (N = 1,427) indicated that experiencing violent and nonviolent negative life events and being exposed to a disaster were inversely associated with adolescents' positive health assessments. As social support and self-efficacy decreased, adolescents' health asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
0
23
1
4
Order By: Relevance
“…21,44,45 Other factors identified as risk factors for violence perpetration in this study such as weapon carrying, illicit drug use, and suicide attempts have also been identified in other studies. 6,16,20 Whereas previous studies have identified low self-efficacy as a risk factor for peer violence, 8,13 this study found low self-efficacy to avoid violence as a protective factor for peer violence, which needs to be examined in more detail in future research.…”
Section: Discussionmentioning
confidence: 67%
“…21,44,45 Other factors identified as risk factors for violence perpetration in this study such as weapon carrying, illicit drug use, and suicide attempts have also been identified in other studies. 6,16,20 Whereas previous studies have identified low self-efficacy as a risk factor for peer violence, 8,13 this study found low self-efficacy to avoid violence as a protective factor for peer violence, which needs to be examined in more detail in future research.…”
Section: Discussionmentioning
confidence: 67%
“…Individuals with higher levels of perceived self-efficacy trust their own abilities in the face of adversity, tend to conceptualize problems as challenges rather than as uncontrollable situations, experience less negative emotional arousal during demanding tasks, think in self-enhancing ways, motivate themselves, and show perseverance when confronted with difficult situations (Bandura, 1997;Luszczynska, Gutiérrez-Doña, & Schwarzer, 2005). Cheever and Hardin (1999) interviewed 1427 adults to find out whether they were exposed to violent traumatizing experiences (such as physical assault, rape, or being held up with a weapon), or to nonviolent traumatic experiences (such as repeating a school grade, changing to a Anxiety, Stress, & Coping 241 new school, or experiencing a natural disaster) during the previous year. They found that higher levels of general self-efficacy were accompanied by lower self-reported health problems in this population.…”
Section: Posttraumatic Stress Responsesmentioning
confidence: 99%
“…Research assessing coping self-efficacy within traumatic stress environments has found these perceptions to be strongly predictive of psychological adjustment to a variety of traumatic stressors. These include natural disasters (Benight and Harper, 2002;Benight et al, l997, l999a,b;Cheever and Hardin, 1999), terrorist attacks (Benight et al, 2000), death of a spouse (Benight et al, 2001;Lindstrom, 1997), and military combat (Solomon et al, 1988(Solomon et al, , 1991. To address the unique symptomatology after a natural disaster, the Hurricane Coping Self-Efficacy (HCSE) measure was created by a team of disaster recovery experts, psychiatrists and psychologists, as well as hurricane victims.…”
mentioning
confidence: 99%